Analisis Penerimaan Masyarakat Kota Salatiga terhadap Fintech ShopeePay dengan Technology Acceptance Model - Alwin Adi Putra; Yessica Nataliani (Faculty of Mathematics and Natural Sciences Sam Ratulangi University, 2023)
Online shopping has become increasingly popular for many people in Indonesia since the Covid-19 pandemic took hold. Shopee is one of the most popular online buying and selling applications. Based on a survey conducted by App Annie, Shopee has been named the most popular marketplace in Indonesia regarding the number of active users and the volume of monthly visits. Shopee has a fintech called Shopeepay. Technology Acceptance Model (TAM) was used to analyze user acceptance during the Covid-19 pandemic. 100 ShopeePay users were taken as a sample using a purposive sampling technique, collected by questionnaire. Determination of the number of samples refers to the number of samples used in previous studies relevant to this research. The analytical techniques used in this study include regression analysis (simple and multiple) and path analysis. The analysis results from the Technology Acceptance Model show that the factors influencing the acceptance of ShopeePay fintech during the Covid-19 pandemic in Salatiga were Perceived Usefulness and Perceived Ease of Use. These two perceptions of TAM influence Attitude toward Using and Behavioral Intention to Use, which impacts Shopeepay's Actual System Usage during the Covid-19 pandemic.